Games and truths: learning to construct social problems in high school debate. - Fine, Gary Alan (Sociological Quarterly)
Although social constructionists have taken the process by which people learn to present social problems for granted, these skills are acquired in the course of socialization. Through high school debate, adolescents acquire techniques for making arguments, using evidence, and presenting claims to multiple audiences. In the process, they learn that taking a public position does not necessarily require a deeply held commitment. This model resonates with the institutional structure of politics and law in the United States in which adversaries battle each other in a rule-governed “game,” a contest ultimately evaluated by judges assumed to be impartial. To understand the process by which adolescents gain the skills to construct social problems I conducted an ethnographic study of debate teams at two high schools. The ability to take both sides of an argument, express ideas with which one does not personally agree, and present powerful, if questionable, evidence, constrained by time, teaches teenagers how to engage in social problem discourse and provides a training ground for moral entrepreneurs. Reprinted by permission of the publisher.